Results of treatment of 20 Iraqi Patients with Newly Diagnosed High and Intermediate grade Non-Hodgkin’s Lymphoma with VACOP-B - Jawad, Ali M.; Al-Khalisi, Khdhair A.; Abbas, Mohamed S. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: CHOP regimen was the standard treatment for patients with diffuse large and mixed cells Non-Hodgkin’s lymphoma (NHL) even in comparison with second and third generation regimen. Recently Rituximab –CHOP is considered the standard treatment for aggressive B-cell NHL while CHOP (alone) is so for aggressive T-cell NHL, yet more than one study investigates another regimen which is VACOP-B and some showed its superiority over CHOP. Prior to the introduction of Rituximab, we used VACOP-B in the treatment of high &intermediate grade NHL in adult Iraqi patients as an alternative to CHOP. Patients and Methods:We performed a prospective analysis of 20 adult patients who, between April 2000 and October2005, received VACOP-B chemotherapy for high and intermediate grade NHL. The weekly regimen consisted of: doxorubicin50 mg/m2 i.v. weeks 1,3,5,7,9,11; cyclophosphamide350 mg/m2 i.v. weeks 1, 5, 9; etoposide 100mg/m2iv, weeks 3,7,11; vincristine1.4 mg/m2 i.v. (2 mg max.) weeks 2, 4, 6, 8, 10;bleomycin 10 mg/m2 i.v.(max. 15 mg) weeks 2,4, 6,8, 10; methotrexate12.5 mg intratheical was given in selected patients.; prednisolone 60mg p.o.daily for 2 weeks, reduced to 60 mg every other day for 10weeks.The patients treated were aged 25-50 years, 8(40%) had high grade (Working Formulation )NHL; 12 (60%) had intermediate grade NHL;seventeen patients(85%) had Stage III/IV disease; and 3 (15%) had stage II,bone marrow involvement seen in 3(15%)patients .patients distribution regarding age adjusted international prognostic index(aaIPI)was 8(40%)with aaIPI 0,1and 12(60%)with 2,3. Follow-up time from completion of VACOP-B chemotherapy ranged from 6 months to 40 months (median 22). Results: VACOP-B induced a complete response (CR) and partial response (PR) in 70% and 15% respectively, whilst one patient had no response to treatment and died due to progression of the disease, 2 patients died due to treatment related toxicity. The three year disease free survival (DFS) was 78%, where 4 patients relapsed, one of them in the central nervous system. This study showed 3-year overall survival (OS) 100% for those with a IPI 0-1and 48% for those with aa IPI 2-3. Tolerance to treatment was measured by WHO toxicity scores. The hemoglobin (Hb) toxicity median score for all patients was grade 1 (Hb 9.5-10.9 g/dl), and the white cell count (WCC), toxicity score was grade 2(WCC 2.0-2.9 x 109/1). No platelet toxicity was observed. Ten per cent of patients suffered grade 3 severity infections requiring antibiotics and there was two treatment related death. Conclusions: VACOP-B chemotherapy is an effective regimen for high and intermediate grade NHL, with an encouraging result in patients with aaIPI 0, 1. although chemotherapy was given weekly, the tolerance to treatment was acceptable. Studies comparing VACOP-B vs. CHOP chemotherapy to decide the exact role of the first in treating high grade &intermediate grade NHL, in the absence of Rituximab, are still needed.